2017
DOI: 10.1002/polb.24334
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and rheological investigation of self-healable deferoxamine grafted alginate hydrogel

Abstract: Deferoxamine grafted alginate (SA‐DFA) was successfully synthesized via amidation of sodium alginate with deferoxamine mesylate as determined by H‐NMR and elemental analysis. SA‐DFA with different graft yield was obtained by adjusting the ratio of sodium alginate and deferoxamine mesylate. It was found that aqueous solution of SA‐DFA could form hydrogel spontaneously due to hydrogen bonding interactions, which also endowed the SA‐DFA hydrogel with self‐healing capability. The healing efficiency of SA‐DFA hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For all tested groups, it can be observed that G ′ and G ′′ are almost independent of the applied frequency from 0.1 to 2 Hz. Moreover, it was found that G ′ > G ′′ during all tested frequencies, which suggested a solidlike mechanical response. , At frequencies higher than 2 Hz, both G ′ and G ′′ increased, indicating a superior structural organization of the hydrogel network. , …”
Section: Resultsmentioning
confidence: 83%
“…For all tested groups, it can be observed that G ′ and G ′′ are almost independent of the applied frequency from 0.1 to 2 Hz. Moreover, it was found that G ′ > G ′′ during all tested frequencies, which suggested a solidlike mechanical response. , At frequencies higher than 2 Hz, both G ′ and G ′′ increased, indicating a superior structural organization of the hydrogel network. , …”
Section: Resultsmentioning
confidence: 83%
“…3 b). The high mechanical properties of F-DFO-SA/BG hydrogel may be attributed by the newly formed hydrogen bond formation between DFO and SA [ 34 ]. The amine and carbonyl groups on the DFO could form hydrogen bond with the hydroxyl groups on the SA.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen bonding has been used to achieve temperature responsiveness of self-healing hydrogels [ 73 ]. For example, the hydrogen bonding via freezing method has been used to develop the polyvinyl alcohol-based self-healing hydrogels [ 74 ].…”
Section: Self-healing Polymers In Medical Applicationmentioning
confidence: 99%